PERANCANGAN BUKU SENJATA KURAMBIK KHAS MINANGKABAU SUMATERA BARAT - Ferry Fernando (DeKaVe, 2013)
The design of typical Minangkabau book kurambik weapon, aim to be expected to be acomplete visual documents about weapons kurambik I kerambit Minangkabau and can be used as areference in teaching and research. It also aims to maintain continuity kurambikweapons and maintainedon an ongoing basis as a product of the culture of Indonesia. This book is one way to be able to keepkurambik remain in the State of Indonesia.This book is based on the use of photo etnofotografi which is more likely than artistic. Becauseetnofotografi is the study of a culture of a society with the help of photos in it. Picture elements should beable to describe the social structure, dominance, social class and other cultural symbols. Etnofotografirooted in ethnography.Minangkabau kurambik book "IndakLakang DekPaneh, IndakLapuakDekHujan "comes as agap filler kurambik media about guns that had not been there. The book is expected to be a reference andteaching materials also stimulated interest in research to examine kurambikweapons.Keywords: Design books, Etnofotografi, Weapons kurambik